PENGADAAN TAMAN BACA UNTUK MENINGKATKAN SEMANGAT MEMBACA SISWA MI HIDAYATULLAH DESA PRINGU BULULAWANG KAB. MALANG - Nur Hidayah, Detri; Jariyah, Ainun; Fitri, Raisa (Transpublika Publisher, 2021)
Literacy is defined as the capacity for reading and writing. Reading is an activity that entails comprehending texts in order to glean information from them. Reading can significantly increase kids' ability to develop conclusions from the information they absorb. By not reacting too fast, we can encourage pupils to think critically. Assisting pupils in expanding their knowledge through reading. Helping to increase students' knowledge by reading. Among elementary school students or students reading activities are still very lacking, especially in MI Hidayatullah Pringu Village, Bululawang District, Malang Regency, therefore we created a reading garden program with the aim of increasing the reading enthusiasm of students in MI Hidayatullah Pringu Village. The methods used in this research are surveys, consultation with school principals and implementation. Activities carried out by donating books, then cleaning the library followed by arranging and making a reading garden. After the program, according to the survey, the attendance of students who came to the library increased from before and after the reading garden.